Developing Students' Literacy and Numeracy Skills in the School Environment - Krisdianti, Nining; Hani, Darfi; Raya, Fitri; Sukaisih, Rosisa (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to explore deeper understanding of effective ways to develop literacy and numeracy skills in the school environment. The writing of this article uses a literature review research method, which is carried out by collecting various relevant research articles on the topic of developing literacy and numeracy in students in schools. In this study, researchers inventory relevant concepts to understand how numeracy skills can develop in students and the factors that influence them in the school environment. The results of the literature study found that various effective ways to develop literacy and numeracy skills in the school environment, such as project-based approaches and educational games, supportive classroom and school environments, targeted teaching strategies, interactive and participatory learning programs, SSI-based Student Worksheets (LKPD), Mobile Mathematics Pathways, which combine technology with the PBL model, the AKSI application (Indonesian Student Skills Application), storytelling programs, reading, writing and arithmetic lessons, and the use of learning media. However, developing students’ literacy and numeracy skills in various educational contexts faces a number of complex challenges, the main constraints of which include resource constraints, differences in levels of student engagement, and the need for adequate policies and training.